The Effect of Products and Prices on Purchasing Decisions of Health Food - Suharso, Arien Anjar Puspitosari (Faculty of Economics, State Islamic University of Maulana Malik Ibrahim Malang, 2020)
This study aims to analyze and explain the effect of products and prices on purchasing decisions of health food in Malang both partially and simultaneously. The approach uses quantitative-explanatory methods. The population is Malang City Consumer in Blimbing, Kedungkandang, Klojen, Lowokwaru and Sukun Subdistricts. The samples are 384 respondents. The collected data is analyzed by multiple linear regressions with SPSS software version 22. The study results are follows. First, products partially affect on purchase decision of health food. Second, the prices can improve purchase decision of health food. Third, the price becomes the determining factor in purchase decision of health food.